EKSISTENSI PURA DALEM BLEMBONG DI KAMPUS UNIVERSITAS UDAYANA DESA ADAT JIMBARAN: (Persepektif Teologi Hindu) - I Made Dirghayusa Mendala (Pangkaja: Jurnal Agama Hindu, 2023)
Hinduism has a holy place called Temple as a worship to Ida Sang Hyang Widhi Wasa and one way to achieve harmony and mutual prosperity, in Hinduism it is called Tri Hita Karana. The role of the Temple as a Hindu is so important, while the Udayana University in Jimbaran Traditional Village pleads for safety every day by itself a temple called Dalem Blembong Temple. Early observations, the existence of this temple was made as a worship to ask for fertility in agriculture by several family groups in the 1950s. In 1990 the Udayana University built the Rectorate Building to the south of Dalem Blembong Temple. After the Rectorate Building was established, several days later conflicts occurred, in the end Udayana University went to a smart person to ask for instructions. Smart people advise to perform the ultimate guidance ceremony which was buried under the Rectorate Building by Udayana University when building the Rectorate Building to be taken to Dalem Blembong Temple. After the guidance process and participating in managing the existence of Dalem Blembong Temple, conflicts began to decrease and interactions began to create interactions between staff within the scope of Udayana University. Based on the background above, the author wants to explore and re-confirm the problem according to the initial observations with the phenomena he experienced. The problems that will be studied in this scientific paper from the perspective of Hindu theology include: (1) What is the function of the Dalem Blembong Temple on the Udayana University Campus, Jimbaran Traditional Village?, and (2) What are the implications of the Dalem Blembong Temple on the Jimbaran Traditional Village Udayana University Campus?. This scientific work uses a qualitative research type, collecting informants using purposive and collected using participant observation techniques, document studies, and literature studies. After the data was collected, it was analyzed using a qualitative descriptive technique. So that the results obtained after analyzing the data are in accordance with the formulation of the problem above, including: (1) Functions of Dalem Blembong Temple (2) Theological implications of Dalem Blembong Temple, and (3) Implications of Environmental Preservation of Dalem Blembong Temple. Keywords: The Existence, Dalem Blembong Tample, Theology Hindu